Anterior sagittal anorectoplasty with external sphincter preservation for the treatment of recto-vestibular fistula: A new approach - Mohamed Ibrahim Elsawaf; Mohamed S Hashish (Wolters Kluwer Medknow Publications, 2018)
Context: To our knowledge, there is no description of anterior sagittal anorectoplasty (ASARP) with external anal sphincter preservation and passing neorectum in the middle of muscle complex under direct vision for the treatment of recto-vestibular fistula (VF). Aim: This study evaluates a new modification combining ASARP with under vision sphincter preservation. Subjects and Methods: This prospective study was conducted on thirty female infants with VF. Procedure starts with a vertical midline incision extending from ectopic opening to posterior limit of external sphincter. Sharp dissection of the fistula is carried out. Artery forceps is passed at the center of muscle complex under vision, then neorectum is placed in the middle of the muscle complex. We introduced a new scoring system based on parental interview assessing functional outcome. Each patient was given a score between 0 and 20; good: 14-20, fair: 7-13, and poor: 0-6. Results: ASARP was performed at a mean age of 2.6 months, a mean weight of 5.2 kg, a mean operative time of 102 min, and a mean hospital stay of 3.6 days. Wound infection occurred in four cases, seven cases had perianal excoriations, six cases had anal stenosis, and only one case complained of anal displacement. Patients followed for a mean of 18.8 months. Majority of our patients (50%) had good score (mean = 16.8), normal frequency, no or mild soiling, normal anal position with no or mild stenosis. Fourteen patients had fair score (mean = 10.5). Only one had poor outcome with severe soiling and perineal excoriation. Conclusion: Our modification offers optimal correction, with minimal sphincteric damage, without additional complexity or difficulties. Scoring system is simple, practical, and truly reflects early functional and parent satisfaction after surgery.